2023
DOI: 10.3390/v15122333
|View full text |Cite
|
Sign up to set email alerts
|

Viral Components Trafficking with(in) Extracellular Vesicles

Félix Rey-Cadilhac,
Florian Rachenne,
Dorothée Missé
et al.

Abstract: The global public health burden exerted by viruses partially stems from viruses’ ability to subdue host cells into creating an environment that promotes their multiplication (i.e., pro-viral). It has been discovered that viruses alter cell physiology by transferring viral material through extracellular vesicles (EVs), which serve as vehicles for intercellular communication. Here, we aim to provide a conceptual framework of all possible EV-virus associations and their resulting functions in infection output. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 126 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…DENV envelop contains lipids, which composition partially varies when viruses derive from mosquito or mammalian cells 57,58 . To evaluate the impact of DENV-lipids on DENV infection, we produced DENV in mosquito and monkey cells, and isolated virions from EVs 59 using discontinuous sucrose density gradient. The purified DENV samples were obtained from our previously-published study, which reported an absence of EV markers (i.e., Alix) in the DENV density fraction 58 , suggesting at least partial separation of DENV from Alix-containing EVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DENV envelop contains lipids, which composition partially varies when viruses derive from mosquito or mammalian cells 57,58 . To evaluate the impact of DENV-lipids on DENV infection, we produced DENV in mosquito and monkey cells, and isolated virions from EVs 59 using discontinuous sucrose density gradient. The purified DENV samples were obtained from our previously-published study, which reported an absence of EV markers (i.e., Alix) in the DENV density fraction 58 , suggesting at least partial separation of DENV from Alix-containing EVs.…”
Section: Resultsmentioning
confidence: 99%
“…However, infection was similarly enhanced when cells were supplemented with lipids from mock-infected mosquito cell supernatant. Since EVs and DENV have partially overlapping density 59,60 , the mock-infected fraction probably contained EVs, which did not possess or had undetectable amount of the EV marker 58 and the increased infection upon supplementation with mock-infected lipids was likely caused by residual mosquito EV-lipids. In contrast, supplementation with either DENV or mock-infected lipids from mammalian cells did not alter DENV infection (Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…The hijacking of exosome biogenesis might additionally confer the ability of viruses to target crucial components within exosomes, including their own viral nucleic acids, as well as viral proteins or even complete virions. This was notably shown with the hepatitis B virus (HBV) [ 132 ], and since the role of EVs in infections has been studied, examples of viruses using host exosomes as transport systems for their factors have become widespread and are regularly and recently the subject of comprehensive reviews [ 133 , 134 ]. This ability has led to a Trojan Horse hypothesis that exosomes actively contribute to infectious pathogenesis, helping some viruses to evade immune system recognition and sometimes facilitating viral persistence [ 135 ].…”
Section: Exosomes and Biology Of Infectionmentioning
confidence: 99%
“…The hijacking of exosome biogenesis might additionally confer the ability to viruses to target crucial components within exosomes, including their own viral nucleic acids, as well as viral proteins or even complete virions. This was notably shown with the hepatitis B virus (HBV) [136] and since the role of EVs in infections has been studied, examples of viruses using host exosomes as transport systems for their own factors have become widespread and are regularly and recently the subject of comprehensive reviews [137,138]. This ability has led to a Trojan Horse hypothesis that exosomes actively contribute to viral pathogenesis and sometimes facilitate viral persistence [139].…”
Section: Exosomes Are Small Specialized Extravesicular Vesicles (Evs)mentioning
confidence: 99%